PENEGAKAN HUKUM TERHADAP PELAKU DAN KORBAN TINDAK PIDANA PHISING DI INDONESIA (STUDI KASUS PUTUSAN PENGADILAN NEGERI BANJARBARU NOMOR 85/PID.SUS/2022/PN BJB) - Teguh, Ady; Anita Sinaga, Niru (MALA IN SE: Jurnal Hukum Pidana, Kriminologi, dan Viktimologi, 2024)
Cybercrime nowadays involves obtaining personal identification data such as user IDs and passwords using phishing techniques. There is a distinction between theft in cyberspace, which generally begins with data theft. The stolen data is then used to commit actions that harm the victim. The issue is how phishing crimes are regulated in Indonesia and the legal enforcement against the perpetrators and victims of phishing crimes in the Banjarbaru District Court Decision No. 85/Pid.Sus/2022/PN Bjb. The purpose of this research is to understand the regulation of phishing crimes and the legal enforcement against the perpetrators and victims in the Banjarbaru District Court Decision No. 85/Pid.Sus/2022/PN Bjb. This research uses a normative method, which is conducted by analyzing written laws from literature or secondary data. The results of this study conclude that the regulation of phishing crimes refers to Law No. 19 of 2016 concerning Amendments to Law No. 11 of 2008 on Electronic Information and Transactions. Law enforcement related to cybercrime is still relatively light and not proportional to the losses experienced by the victims. As in Decision No. 85/Pid.Sus/2022/PN Bjb, the defendant was sentenced to two years and six months in prison and fined Rp 500,000,000.00 (five hundred million rupiah). This is not in line with the provisions set out in Law No. 27 of 2022 on Personal Data Protection. The recommendation of this research is that the government and society should understand the importance of protecting personal data and properly implement Law No. 27 of 2022 on Personal Data Protection to guarantee privacy rights. The establishment of a special and independent authority to address personal data issues is also suggested.